Decision Support System for Millennial Generation Softskill Competency Assessment using AHP and Eliminate Promethee Method - Akmaludin, Akmaludin; Sihombing, Erene Gernaria; Dewi, Linda Sari; Rinawati , Rinawati; Arisawati, Ester (Sinkron : jurnal dan penelitian teknik informatika, 2021)
The current millennial generation has the soft skills needed to follow the trends and technology of the industrial generation 4.0. It is clear that many Millennials look more energetic and always synergistic with destructive situations and conditions. Industry 4.0 generation makes the business world switch to always using advanced technology in various sectors so that technological progress is felt faster than before, and human power is starting to be replaced by machine power, robotics, and even artificial intelligence. Thus, soft skills for the millennial generation are needed to get job opportunities in conditions where the need for human labour has begun to be eliminated in their work. The purpose of this paper is to assess the soft skills competencies possessed by the millennial generation, who are always involved with technological advances in the very fast business industry world. There are eight soft skills that the millennial generation must possess, namely critical thinking, communication, analyzing, creative and innovation, leadership, adaptation, cooperation and public speaking. The method used to select soft skills competencies for job opportunities for the millennial generation is the Analytic Hierarchical Process (AHP) method in collaboration with the Promethee elimination method. The final result of the decision support for soft-skill competency selection from 23 millennial generations, who passed the selection, was 43% (10 users) with a positive score and 57% (13 users) who experienced selection failure. This failure was due to having a negative score. Thus, the collaboration of the AHP and Promethee Elimination methods can provide optimal results for decision-making support.